STUDIES ON BIOCHEMICAL CONSTITUENTS OF DIFFERENT GENOTYPES OF MORUS ALBA L. - M.JYOTHI; M.PRATAP; S.THIMMA NAIK (International Journal of Pharma and Bio Sciences, 2014)
Growth and development of silk worm Bombyx mori L. and cocoon crop are greatly influenced by yield and nutritional quality of mulberry leaf used as feed. The nutritional status of different mulberry varieties is ascertained by its biochemical constituents. Mulberry is rich sources of protein, carbohydrate, carotenoids, lipids, ascorbic acid, anthocyanins etc Hence, five mulberry varieties viz., M5, RFs-135, V1, S36 and S13 were analysed for their leaf quality through phytochemical tests. Results reviled that V1 is the best one containing highest total soluble protein (111.40mg/g), total free amino acid(9.88µg/g) and total phenol(4.96%) contents compare to other four varieties, so V1 is the highly recommendable feed for silkworm (Bombyx mori L) to increase their silk productivity.